The social life of opium in China - Zheng, Yangwen (Cambridge University Press, 2005)
"In a broad-ranging narrative, Zheng Yangwen's book explores the history of opium consumption in China from 1483 to the late twentieth century. The story begins in the mid-Ming dynasty, when opium was sent as a gift by vassal states and used as an aphrodisiac in court. Over time, the Chinese people from different classes and regions began to use it for recreational purposes, so beginning a complex culture of opium consumption. The book traces this transformation over a period of 500 years, asking who introduced opium to China, how it spread through all sections of society, embraced by rich and poor alike as a culture and an institution. The book, which is accompanied by a fascinating collection of illustrations, offers a vivid and alternative perspective on life in China, which will be embraced by students of history, anthropology and sociology, and all those with an interest in China."--Jacket.